2015
DOI: 10.7883/yoken.jjid.2014.202
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis of Activities of 16 Antimicrobial Agents against Gram-Negative Bacteria from Six Teaching Hospitals in China

Abstract: SUMMARY:To evaluate the in vitro antimicrobial activities of biapenem, arbekacin, and cefminox against different gram-negative bacterial isolates in China, a total of 100 non-duplicated Escherichia coli, 100 Acinetobacter baumannii, 100 Pseudomonas aeruginosa, and 99 Klebsiella pneumoniae isolates were collected from 6 teaching hospitals in China in 2012. The minimal inhibitory concentrations (MICs) of biapenem, arbekacin, cefminox and 13 other antibiotics were determined by the broth microdilution method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(17 reference statements)
2
1
0
Order By: Relevance
“…Our results are similar, to some extent, to those reported by Jones et al (Jones et al, 2002), Iroha et al(Iroha et al, 2015), Cho et al(Cho et al, 2015), Chen et al(Chen et al, 2015) who found that carbapenems (biapenem, meropenem and imipenem) exhibited high antimicrobial activities against Gram-negative bacteria especially E. coli and Klebsiella pneumoniae. Also Turner examined the activity of meropenem against a total of 5208 isolates of Enterobacteriaceae; the susceptibility rate for meropenem was (99.4%).…”
Section: Resultssupporting
confidence: 92%
“…Our results are similar, to some extent, to those reported by Jones et al (Jones et al, 2002), Iroha et al(Iroha et al, 2015), Cho et al(Cho et al, 2015), Chen et al(Chen et al, 2015) who found that carbapenems (biapenem, meropenem and imipenem) exhibited high antimicrobial activities against Gram-negative bacteria especially E. coli and Klebsiella pneumoniae. Also Turner examined the activity of meropenem against a total of 5208 isolates of Enterobacteriaceae; the susceptibility rate for meropenem was (99.4%).…”
Section: Resultssupporting
confidence: 92%
“…However, the results of these studies showed that biapenem combined with fosfomycin yielded higher percentage of synergism than the other carbapenems (biapenem 34.18%, imipenem 29.11%, meropenem 27.43% and doripenem 23.63%). The higher MIC50 and MIC90 of A. baumannii for biapenem and fosfomycin in teaching hospitals were consistent with studies in China [27][28] .…”
Section: Discussionsupporting
confidence: 88%
“…Though colistin exhibited high antimicrobial activities against GNB, including E. coli, A. baumannii, Pseudomonas aeruginosa isolates, and K. pneumonia in human (Chen et al, 2015), the frequent presence of mcr-1 -positive E. coli and in food animals might be a threat to human. As colistin is the last therapeutic option against infections caused by MDR GNB, careful monitoring of the evolution of colistin resistance and the spread of mcr-1 gene in isolates from humans in China is urgently needed.…”
Section: Resultsmentioning
confidence: 99%